Non-peripherally tetra substituted lead(II), nickel(II) and copper(II) phthalocyanines bearing [1,2,3] triazole moeties: Synthesis, characterization and investigation of electrochemical and spectroelectrochemical properties - KOCA, ATIF (ELSEVIER SCIENCE BV, 2019)
In this study, the synthesis and characterization of novel [1,2,3] triazole substituted phthalonitrile compound (3) and non-peripherally tetra 3-(2H-benzo[d][1,2,3]triazol-2-yl)-4-hydroxyphenethyl methacrylate substituted lead(II) (4), nickel(II) (5) and copper(II) (6) phthalocyanine derivatives were achieved. The new compounds were characterized by using FT-IR, H-1-NMR, C-13-NMR, UV-Vis and mass spectra. The electrochemical properties of novel non-peripherally tetra [1,2,3] triazole substituted metallo phthalocyanines (4-6) was determined by cyclic voltammetry (CV) and square-wave voltammetry (SWV) for the first time in this study. The results show that all the complexes (4-6) have ligand-based diffusion controlled electron transfer properties. The color changes related to the redox processes were also recorded with in-situ electrocolorimetric measurements. When the spectral changes are compared with each other, it is clear that all complexes show Pc based electron transfer reactions. There are slight differences between the spectra of the complexes due to the different nature of the metal centers of the complexes. The electrochemical and in-situ UV-Vis spectral change of complexes (4-6) indicated that they have applicability in electrochemical technologies. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; [1,2,3] triazole; Electrochemistry; Spectroelectrochemistry; LU(III) PHTHALOCYANINES; METALLO-PHTHALOCYANINES; ELECTRICAL-PROPERTIES; METALLOPHTHALOCYANINES; DERIVATIVES; SURFACE; AGENTS; REDOX; FILMS; 1,2,3-BENZOTRIAZOLE